Eksperimentasi dan Eksplorasi Instrumen Tiup Bayu Akasa Oleh Mugiyono Kasido - Ananda Tri Ariska; Kiswanto Kiswanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to reveal the creative process behind the creation of the Bayu Akasa instrument, an organological innovation based on bamboo by contemporary artist Mugiyono Kasido. Through a qualitative approach using case study methods, this study examines two crucial stages in the creation of the work, namely the material exploration phase and the experimentation with physical techniques. Data was collected through in-depth observation of the subject's performance, documentation of the rehearsal process, and interviews regarding the philosophical and technical aspects of sound production. The results of the study show that: (1) The material exploration stage produced a 2-meter-long aerophone instrument made of petung bamboo with a diameter of 5.9–7.9 inches, designed with an integral three-part system; (2) The experimentation with playing techniques focused on mastering circular breathing or ngunjal, which enables the production of continuous meditative drone sounds without pause; (3) This innovation represents a blurring of the boundaries between choreographic and musical aspects, in which the instrument is no longer treated as a static object but as a somatic extension of the artist's body. These findings confirm that Bayu Akasa is not just an ordinary wind instrument, but a representation of space (Akasa) and breath (Bayu) manifested in a radical performative unity. This research contributes to the development of contemporary organology based on local materials in Indonesia.